2014
DOI: 10.1200/jco.2013.49.8386
|View full text |Cite
|
Sign up to set email alerts
|

TMPRSS2:ERG Gene Fusion Predicts Subsequent Detection of Prostate Cancer in Patients With High-Grade Prostatic Intraepithelial Neoplasia

Abstract: A B S T R A C T PurposeHigh-grade prostatic intraepithelial neoplasia (HGPIN) is considered a precursor lesion of prostate cancer (PCa). The predictive value of ERG gene fusion in HGPIN for PCa was interrogated as a post hoc analysis in the context of a randomized clinical trial. Patients and MethodsThe GTx Protocol G300104 randomly assigned 1,590 men with biopsy-diagnosed HGPIN to receive toremifene or placebo for 3 years or until a diagnosis of PCa was made on prostate biopsy. As part of this phase III clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 28 publications
6
68
0
2
Order By: Relevance
“…As for prostate cancer, TMPRSS2:ERG may be a key step in the early stage of prostate cancer development. It was reported that the patients with high-grade prostatic intraepithelial neoplasia (HGPIN) who overexpressed ERG were more vulnerable to prostate cancer than their counterparts without ERG expression [30]. Over the past decade, accumulating evidence demonstrated that TMPRSS2:ERG fusion gene can be a potential tumor biomarker for detecting prostate cancer, particularly in Western countries [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…As for prostate cancer, TMPRSS2:ERG may be a key step in the early stage of prostate cancer development. It was reported that the patients with high-grade prostatic intraepithelial neoplasia (HGPIN) who overexpressed ERG were more vulnerable to prostate cancer than their counterparts without ERG expression [30]. Over the past decade, accumulating evidence demonstrated that TMPRSS2:ERG fusion gene can be a potential tumor biomarker for detecting prostate cancer, particularly in Western countries [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…TMPRSS2-ERG fusions are the most common molecular alteration in prostate cancer, occur-ring in 40% -50% of tumors The Cancer Genome Atlas Research Network 2015). These fusions are also recognized in isolated high-grade prostatic intraepithelial neoplasia (HGPIN) lesions (Park et al 2014), lesions associated with cancer (Perner et al 2007), as well as benign prostatic epithelial cells after extended exposure to DHT (Berger et al 2011), suggesting that the acquisition of TMPRSS2-ETS fusions is likely an early carcinogenic event. Moreover, some evidence suggests that androgens themselves can provoke nonrandom fusion events (Lin et al 2009;Mani et al 2009).…”
Section: Androgen Receptor Actionmentioning
confidence: 99%
“…[45][46][47] There is potential clinical significance to these findings, since isolated HGPIN with ERG overexpression on biopsy has been shown to have a higher rate of cancer on repeated biopsy than isolated HGPIN without ERG overexpression. 48,49 While most HGPIN cases likely represent a precursor lesion, a recent and robust study by Haffner et al 50 has shifted this paradigm; by examining ERG rearrangements in addition to PTEN deletion to track the temporal evolution of HGPIN and invasive carcinoma, the authors demonstrated that in some cases, HGPIN arises from nearby invasive cancers, likely through retrograde colonization. Distinguishing such cases where HGPIN may represent progression of disease is clinically important and further work likely is needed in this area.…”
Section: Molecular Characteristics Of Hgpinmentioning
confidence: 99%